Perancangan Mobile Crane Kapasitas 2 Ton Sebagai Sarana Penunjang Galangan Reparasi - Bagus Fatahhillah; I Putu Sindhu Asmara; Ali Imron (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
In a repair shipyard company there is a constraint, which in the field conditions require adevice that can be used to lift objects or goods that have a small capacity and can reach the height ofthe deck from the ship. But in the lifting products that already exist, when it has a small capacity thenhas a small lift height. And when it wants to take a lift height as its lift capacity also rises based onthe above problems it is necessary to design a new lift tool that can meet those needs.In this research,the lifting equipment is a mobile crane. So that it can be moved as well as the effectiveness of theplace of the shipyard. To meet the lift strength and lift level needed, it is necessary to analyze thestrength of the structure using the finite element method or FEM.In the design is expected to help forthe improvement and addition of existing facilities in the shipyard in Indonesia. In the results of theresearch, there are still some disadvantages, namely that in some calculations below the deck areignored, so that in the future there needs to be a calculation under the deck from the mobile crane.